Transformational learning for health professionals through a Theatre of the Oppressed workshop. Issue 4 (13th October 2019) - Singh, Satendra; Kalra, Juhi; Das, Sanjoy; Barua, Purnima; Singh, Navjeevan; Dhaliwal, Upreet
Abstract : Theatre of the Oppressed (TO) is a powerful participatory tool for communities to examine their struggles against oppression. The healthcare community has problems inherent to complex, unequal power equations, and TO may be a useful means to understand and respond to their struggle. A 3-day workshop on TO was facilitated by the authors in the Himalayan Institute of Medical Sciences (HIMS) in Dehradun, India, in August 2017. The workshop culminated in the 'Forum Theatre', which included five short plays, each depicting a struggle due to real-life oppression faced by one or the other participant. The audience (about 200 invited members of the HIMS community) chose one play depending on the struggle with which they identified most. That play was 'forumed': spectators were invited to replace the struggling person and demonstrate how they would handle the oppression. Over the next week, participants reflected on the workshop through a structured online questionnaire. The feedback (n=16/27 participants; response rate 59.3%) was subjected to descriptive statistics and to qualitative analysis. The highest average Likert score (out of a maximum of 5) was given to the following items: TO engages senses and emotions (4.6± 0.50), can help inculcate ethical behaviour (4.4± 0.81), identifies conflict (4.4± 0.51), and resolves issues of attitude, behaviour, communication, diversity and empathy (4.4± 0.73). The Forum Theatre was reported to be a means to "express emotions and opinions and to simultaneously gather the same from others"; "make people push their own limits"; "bring out social problems in public"; "examine the root causes behind lived experience"; "provide context for understanding and for exploring alternatives"; and "convert thoughts to action." In conclusion, TO is an engaging activity that identifies conflict; participants' initial reactions suggest that it may initiate change in the ABCDE attributes (attitude, behaviour, communication, diversity, ethics and empathy) of medical professionals.